Nordic Pulp & Paper Research Journal : The international research journal on sustainable utilization of forest bioresources (De Gruyter, 1986)
Nordic Pulp & Paper Research Journal is a peer-reviewed, international scientific journal covering to-date science and technology research in the areas of wood-based biomass: Pulp and paper: products and processes; wood constituents: characterization and nanotechnologies; bio-refining, recovery and energy issues; utilization of side-streams from pulping processes; and novel fibre-based, sustainable and smart materials.